EU Framework for Safeguarding Financial Stability : Towards an Analytical Benchmark for Assessing its Effectiveness - Nieto, Maria (IMF Working Papers; Working Paper ;, 2007)
European finance is becoming increasingly cross-border, while the European architecture for safeguarding financial stability - including decision-making processes for providing financial-stability public goods - have remained decentralized with some explicit mechanisms for coordination across countries. Policy makers are aware of the limitations of the existing institutional setting, but opinions on how to proceed, including on burden sharing, are lining up along national and regional political lines with less attention paid to European needs. This paper applies the 'economics of alliances' to examine these European policy challenges. The paper establishes benchmarks for assessing the ability of Europe's existing institutional architecture to efficiently allocate resources to safeguard the EU financial system against systemic threats to stability, such as the insolvency of a pan European bank.